Professional counseling from a Christian worldview - Evans, Courtney (Journal of spirituality in mental health, 2022)
As the counseling profession has increased focus on spiritual integration into counseling sessions, such integration brings necessary attention to professional ethics. While ethical guidelines mandate that counselors not impose values on clients, this has oftentimes been confused with the false idea that counselors who are Christian may not or cannot practice ethically due to potential conflicts between ethical practice and religious beliefs. This study helps explore professional counselors’ understanding of the integration of Christianity into professional counseling. Such an understanding may help correct biases regarding ethical use of Christianity in professional mental health counseling.